The Effectiveness of Using Tells Strategy on Students’ Reading Comprehension - Aini, Nurul; Suci Apriliani, Nita; Setya Budhi Ningrum, Ary (Universitas Nusantara PGRI Kediri, 2023)
This research aims to find out the significant effect of using TELLS strategy toward students’ reading comprehension. Based on the researcher’s preliminary study, it was found that the students could not comprehend the meaning of texts in their text book at the school. This problem was caused by some factors, some students could not understand about the content of reading text and identify the detailed information of the text. The design of this research was quasi- experimental design, non-equivalent control group design. The total number of populations was 62 students. The researcher used cluster sampling by taking two groups only as sample; group VII-J consisted of 31 students as experimental group and group VII-K consisted of 31 students as control group, totally 62 students. To analyze the data, the researcher adopted ANCOVA formula by using SPSS 21. From calculating the hypothesis test, it is known the result of significant value of group class is 0,023 which is lower than 0,05 (p<.05), therefore there is significant different between experimental and control class. Point out the ANCOVA analysis, the “corrected model” value is reviewed. The result of corrected model is 0,000 which is lower than 0,05 (p<.05). This is also supported by the mean value of the experimental class of 82.45 which is higher than the control class of 66.97. In conclusion, TELLS strategy is more effective on students reading comprehension for the first grade at MTsN 2 Kediri.